2020
DOI: 10.1186/s13550-020-00715-0
|View full text |Cite
|
Sign up to set email alerts
|

[18F]FDG PET/CT for evaluating early response to neoadjuvant chemotherapy in pediatric patients with sarcoma: a prospective single-center trial

Abstract: Introduction This is a prospective, single-center trial in pediatric patients with sarcoma aiming to evaluate [18F]FDG PET/CT as a tool for early response assessment to neoadjuvant chemotherapy (neo-CTX). Methods Bone or soft tissue sarcoma patients with (1) baseline [18F]FDG PET/CT within 4 weeks prior to the start of neo-CTX (PET1), (2) early interim [18F]FDG PET/CT (6 weeks after the start of neo-CTX (PET2), (3) evaluation of neo-CTX response by histology or MRI, and (4) definitive therapy after neo-CTX (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Nevertheless, poor histologic response was significantly associated with lower PFS rates and shorter median PFS compared to the responder group in the Kaplan–Meier survival analysis, similar to the results of previous studies [13,17]. In previous studies, it was reported that the quantitative metabolic-volumetric FDG PET derived parameters were found to be significantly associated with histologic tumor response 13,17,19–21. These studies were generally based on the quantitative values of FDG PET imaging after NAC and the percentage changes between on baseline and post-therapy scans.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, poor histologic response was significantly associated with lower PFS rates and shorter median PFS compared to the responder group in the Kaplan–Meier survival analysis, similar to the results of previous studies [13,17]. In previous studies, it was reported that the quantitative metabolic-volumetric FDG PET derived parameters were found to be significantly associated with histologic tumor response 13,17,19–21. These studies were generally based on the quantitative values of FDG PET imaging after NAC and the percentage changes between on baseline and post-therapy scans.…”
Section: Discussionsupporting
confidence: 84%
“…Nevertheless, PET-CT has an established role in the detection of bone metastases with higher sensitivity compared to bone scans. Several studies suggest that PET may be a promising tool for response to therapy prediction in OS patients [ 72 , 73 ].…”
Section: Imaging Evaluationmentioning
confidence: 99%